Incidence of the economic crisis, regular seasons 2015-2019, on the show and the fans of venezuelan professional baseball: Case of Cardenales de Lara (Gestión y Gerencia, 2023)
The objective of the research was to describe and interpret how the economic crisis during the 2015-2019 regular seasons affected the show and the fans of Venezuelan professional baseball, the Cardenales de Lara case. The study is descriptive, not experimental and documentary. From the results obtained from the analysis of the variables ticket sales and beer consumption affected by inflation, it was evidenced that both decrease as inflation increases and the less fans go to the stadium, the lower the consumption within it. The advertising revenue variable increases each season due to its greater scope, and the behavior of inflation in the study period showed an increase in its percentage variation during the first four seasons and a reduction in it in the last season. In turn, the elasticity of general demand for ticket sales was elastic in the 2016 season with respect to 2015, inelastic in 2017 with respect to 2016, and elastic in the 2018 and 2019 seasons with respect to 2017. and 2018 respectively.
Keywords: Inflation; sales; consumption; advertising